Analysis Of Financial Management And Financial Behavior On The Performance Of Culinary Msmes In Medan City - Vina Gabriella Saragih; Aditiya Pratama Daryana; M. A.Jaya Damanik (Entrepreneurship Faculty, Universitas Garut, 2026)
This study aims to examine the influence of financial management and financial behavior on the performance of culinary MSMEs (Micro, Small, and Medium Enterprises) in Medan City, Indonesia. A quantitative approach was adopted, employing a survey method involving 100 randomly selected MSME owners. Data were collected through structured questionnaires and analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results reveal that both financial management (β = 0.476; p < 0.001) and financial behavior (β = 0.352; p = 0.002) have a positive and significant impact on MSME performance. The model explains 58.1% of the variation in MSME performance (R² = 0.581), indicating a strong explanatory power. The findings highlight the importance of financial literacy, structured bookkeeping, and rational financial behavior in enhancing operational efficiency and business sustainability. The study recommends the implementation of financial education programs and hands-on mentoring to strengthen the competitiveness and resilience of culinary MSMEs